Nemesius of Emesa on Desire, Pleasure, and Sex: A Case of the Medical Making of an Early Christian Sexual Culture - De Wet, Chris L. (Religion & theology, 2021)
This article investigates the views of Nemesius, the bishop of Emesa in Roman Syria at the end of the fourth century CE, on desire, pleasure, and sex, mainly from his work, De natura hominis, asking specifically how Nemesius’s account represents what we might term the “medical making” of an early Christian sexual culture. Nat. hom. was most likely composed at the end of the fourth century CE, and represents the first full and formal Christian anthropology, incorporating views from Christian and non-Christian philosophy (especially Plato and Aristotle) and, of course, extensively utilising (and often even quoting verbatim) ancient medical literature (especially Galen). The study commences by providing a descriptive account of Nemesius’s framework on the dynamics of desire, pleasure, and sex, and then draws some conclusions on how these views of Nemesius translate into a very particular Christian sexual culture in late antique Syria.